The Validity and Readability Test for the Development of PBL-Based UKBM Teaching Materials on the Physics of the Human Circulatory System is Oriented Towards Students' Critical Thinking - Hikmah Fatimah; I Wayan Sumberartha; Agung Mulyo Setiawan (Postgraduate, University of Mataram, 2023)
Indonesia's scientific literacy ability is low with a score of 389. This score can indicate the critical thinking skills of junior high school students. To improve critical thinking can be done by innovating learning tools. For this reason, this research was conducted using the R&D method to develop UKBM which can help students achieve learning mastery. UKBM is part of the learning tools. In this study, UKBM was prepared based on Problem Based Learning (PBL) on the physics of the human circulatory system. So that it can be used by students in learning to enrich their knowledge by oriented towards critical thinking skills. The model used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted during the Covid-19 virus pandemic, so there has been no effectiveness test. The validity of UKBM was obtained through validation of Education Study Program lecturers at FMIPA UM and science teachers at SMPN 8 Malang. The readability test was carried out on 31 students of SMPN 8 Malang grades 9E and 9F who had received material on the physics of the human circulatory system. The percentage of UKBM product validity was 85.41% and the readability test percentage was 87.98%. Based on these results, the PBL-based UKBM on the Physics of the Human Circulatory System Oriented Critical Thinking Skills was declared valid and passed the readability test.